LOCUS OF CONTROL SEBAGAI VARIBEL MODERASI HUBUNGAN KOMPLEKSITAS TUGAS DAN KINERJA AUDITOR - Sri Hastuti; Siti Sundari (Jurnal Keuangan dan Bisnis, 2018)
The research aims to prove the influence of the complexity of the tasks faced by the Auditor on on his or her performance. The complexity of tasks related to various problems in the company requires requires internal and external locuses of control to maintain independence and competence.The first auditor performance case occurred in 2002 with the disclosure of the Enron case involving the KAP in the big five, Athur Anderson. In 2008 the Telkom case affected the closure of KAP Edy Priyanto, and there were still many other cases which were violations of the accountant's code of ethics. This quantitative research attempted to prove the variables of task complexity and locus of control on the auditor’s performance. 46 junior auditors from several KAPs in Surabaya participated in this study. Furthermore, this study employs Partial Least Square test. The study results shows that the complexity of the task affects the performance of the Auditor.